PENDAMPINGAN PENAMAAN KELAS BERNUANSA PRAMUKA SEBAGAI UPAYA PENGUATAN KARAKTER SISWA DI SMA NEGERI 12 MERANGIN - Elsa Ayu Agustina; Hesty Sri Wahyuni; Muhammad Jainuri (Hira Institute, 2025)
Character education is a fundamental aspect of national education aimed at developing students’ abilities while strengthening moral values and social responsibility. However, the implementation of character education through scouting activities is often limited to extracurricular programs and has not been fully integrated into classroom culture. This community service study aims to describe the implementation and impact of mentoring classroom naming with scouting nuances as an effort to strengthen students’ character at SMA Negeri 12 Merangin. A descriptive qualitative approach was employed, with data collected through observation, unstructured interviews with scouting instructors, classroom teachers, and students, as well as documentation of classroom naming and related activities. The program was conducted over one academic semester. Data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that classroom naming based on scouting values contributes positively to the development of students’ discipline, responsibility, cooperation, and social awareness. The integration of scouting values into classroom identity also facilitated teachers in embedding character education into daily learning activities. Overall, mentoring classroom naming with scouting nuances proves to be an effective and sustainable strategy for strengthening character education through school culture.